Anglo-Saxon and Arab Encounters - Idrissi, Achraf (Hungarian Journal of English and American Studies, 2021)
Book review: Stampfl, Tanja. A Century of Encounters: Writing the Other in Arab North Africa. New York: Routledge, 2019. 197 pages. ISBN 9781138363106. Pbk. 155.